Alevi Identity Demands: The Legal and Perceptual Dimensions of the Struggle for Recognition - Talha Köse; Nigar Tuğsuz (İnsan & Toplum)
This study examines the identity-related demands of the Alevi community in Turkey with the statementsof Alevi leaders. There is a set of issues almost all Alevis reach a consensus such as the need for legal status forcemevis, improvement of the status of Alevi dedes, and the abolishing of the mandatory religious education in the primary schools. In this study, it is seen that the main concern and underlying cause of many demands are demands for recognition, accompanied by a struggle for existence and concerns about assimilation. The criticisms that the Alevi society has been discriminated against and the expectations regarding the elimination of discrimination are directly related to all other demands discussed in this study. Despite the AK Party government’s efforts to address the Alevi identity-related requests, the main concerns are still unaddressed. The original data is collected in four separate workshops conducted in four cities of Turkey. Leading figures, especially the Alevi dedes and some of the executives of Alevi foundations and associations participated in the workshops. This study argues that the best approach to address the identity-related requests of Alevis is to increase the stakeholders, incorporate the grassroots level civilian actors and integrate social and political efforts in order to find a lasting solution.